Zinc Iodide Catalyzed Synthesis of 3-Aminoimidazo[1,2-a]pyridines from 2-Aminopyridines and α-Amino Carbonyl Compounds - Han, Xu; Ma, Chaowei; Wu, Zhaoyang; Huang, Guosheng (Synthesis, 2016)
A concise approach to 3-aminoimidazo[1,2-a]pyridines is developed via the zinc iodide catalyzed reaction of 2-aminopyridines and α-amino carbonyl compounds in the presence of oxygen. This novel and user-friendly protocol employing diverse and easily available substrates affords the desired products in good to excellent yields.
Keywords: 3-aminoimidazo[1,2-a]pyridines; zinc iodide; heterocycles; 2-aminopyridines; α-amino carbonyls